2021
DOI: 10.1371/journal.pone.0252229
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals uptake by the global economic crop (Pisum sativum L.) grown in contaminated soils and its associated health risks

Abstract: The aim of the present investigation was to determine the concentration of heavy metals in the different organs of Pisum sativum L. (garden pea) grown in contaminated soils in comparison to nonpolluted soils in the South Cairo and Giza provinces, Egypt, and their effect on consumers’ health. To collect soil and plant samples from two nonpolluted and two polluted farms, five quadrats, each of 1 m2, were collected per each farm and used for growth measurement and chemical analysis. The daily intake of metals (DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
5
28
1
Order By: Relevance
“…These results are in keeping with those reported by Bhardwaj et al (2009), who found that soluble carbohydrate content in Phaseolus vulgaris L plants decreased with increasing concentrations of heavy metals (Pb and Cd). Similarly, Galal et al (2021) found that proteins and carbohydrates declined in the tissues of P. sativum cultivated in soils polluted with heavy metals compared to unpolluted soils. Conversely, lipid concentration increased…”
Section: Agricultural Implicationsmentioning
confidence: 84%
“…These results are in keeping with those reported by Bhardwaj et al (2009), who found that soluble carbohydrate content in Phaseolus vulgaris L plants decreased with increasing concentrations of heavy metals (Pb and Cd). Similarly, Galal et al (2021) found that proteins and carbohydrates declined in the tissues of P. sativum cultivated in soils polluted with heavy metals compared to unpolluted soils. Conversely, lipid concentration increased…”
Section: Agricultural Implicationsmentioning
confidence: 84%
“… Hussain et al., 2019 considered Si to be a growth regulator and played a defensive role against various biotic and abiotic stresses in previous research. Furthermore, Si application may have contributed to improved pea growth performance under stress and non-stress conditions by increasing photosynthesis as indicated by increased chlorophyll levels ( Galal et al., 2021 ). The photosynthetic pigments (Chl a and Chl b) were significantly reduced by Cd toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On an average kangkong had the lowest amount of moisture content compared to other vegetables may be due to the hollow stem and narrow leaves structure (Prasad et al, 2008). From the results it is observed that in most cases the highest dry weight was recorded in untreated waste water (T2), it is may be due to the heavy metals up taken by those vegetable plants (Zhou et al, 2016;Galal et al, 2021). Plant moisture content showed that the water content in the plants which can also show how fresh the plants are (Oulaï et al, 2016).…”
Section: Effect Of Varied Water Treatments On Fresh Dry Weight and Mo...mentioning
confidence: 95%